2018
DOI: 10.12965/jer.1836252.126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diaphragm and deep abdominal muscle exercise on walking and balance ability in patients with hemiplegia due to stroke

Abstract: The aim of this study was to investigate the effects of diaphragm and deep abdominal muscle exercise (DDAME) on walking ability (WA) and balance ability (BA) in subjects with hemiplegia due to stroke. Study subjects consisted of twenty patients diagnosed with hemiplegia due to stroke. They were randomized into a control group (CG) (n=10) that performed traditional exercise and an experimental group (EG) (n=10) that performed DDAME. The WA was measured using the 10-m walking test (10MWT) and 6-min walk test (6M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 29 publications
(32 reference statements)
0
27
0
Order By: Relevance
“…Figure 1 shows the flow details of the trials selected in the different phases. A total of 14 studies were identified for inclusion in the review, totaling 490 participants analyzed 8,27–39 . The characteristics of the studies included are shown on Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 1 shows the flow details of the trials selected in the different phases. A total of 14 studies were identified for inclusion in the review, totaling 490 participants analyzed 8,27–39 . The characteristics of the studies included are shown on Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Some trials compared the effects of core stabilization exercises with those of conventional physical therapies, which included stretching, range‐of‐motion, strengthening, breathing‐enhanced and upper and lower extremity exercises, and passive mobilizations 8,27,28,30,31,34,35 . Other studies include balance and/or gait training 30,33,38,39 . Functional training was used in two studies 28,32 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations